Tindak Tutur Ilokusi Guru dan Siswa pada Pemebelajaran Bahasa Jerman - Musdalifah Musdalifah; Nurming Saleh (Universitas Negeri Makassar, 2023)
Abstract. This study aims to describe the types of illocutionary speech acts between teachers and students in learning German at SMA Negeri 16 Makassar. The research data is in the form of oral speech between the German teacher and class XII IPA 1 students during the learning process. This research is descriptive qualitative. Data collection was carried out through observing, recording and note taking techniques. Data analysis using qualitative data analysis techniques according to Mattew B. Miles and A. Michael Huberman, namely data reduction, data presentation, and conclusions/data verification. The results of the study found that there were four types of illocutionary speech acts during the process of learning German in class XII IPA 1, namely assertive, directive, commissive, and expressive speech acts.Keyword: Illocutionary Speech Acts, Teachers and Students, Qualitative Data Analysis